Composição taxonômica e variações funcionais dos isópodes terrestres (Isopoda: Oniscidea) em habitats epígeos e hipógeos da região Neotropical - Carpio Díaz, Yesenia Margarita (Universidade Federal de São Carlos, 2025)
Subterranean habitats (caves and smaller spaces) represent unique ecosystems that harbor highly specialized species. Exploring functional variations in these habitats provides fundamental clues to understanding diversity patterns, allowing us to learn about the underlying ecological and evolutionary processes, as well as supporting conservation strategies and/or plans. Among the most frequent and abundant organisms in these environments are invertebrates, especially terrestrial isopods, which play essential roles in carbon flow in soils. By acting in the fragmentation of organic matter, these organisms promote nutrient transfer and stimulate microbial metabolism, contributing to increased decomposition rates. The conservation of subterranean habitats is becoming increasingly urgent, since many troglobitic species have restricted geographic distribution, low dispersal capacity, and high sensitivity to environmental disturbances. These factors make them particularly vulnerable to climate change and anthropogenic impacts, such as mining activities, urban expansion, unregulated tourism, and pollution. In this context, research on the characterization of subterranean biodiversity and the assessment of its diversity not only expands scientific knowledge but also strengthens management and conservation actions in tropical karst regions. Given this scenario, the purposes of this project were: (i) to describe the taxonomy of terrestrial isopods associated with subterranean habitats in Colombia; (ii) to describe the taxonomy of these species in epigean and hypogean habitats in southeastern Brazil, with emphasis on the Atlantic Forest biome; and (iii) to evaluate the functional variations of these organisms in epigean and hypogean habitats of the Parque Estadual Turístico do Alto Ribeira (PETAR), southeastern Brazil. To achieve these purposes, specimens deposited in scientific collections were analyzed, including the Laboratório de Estudos Subterrâneos of UFSCar (LES-UFSCar), the Museo de Zoologia da Universidade de São Paulo (MZUSP), and Colección del Laboratorio de Biología de la Universidad de Cartagena (CBUDC). The methodology consisted of a taxonomic review of species from PETAR, SP, and cave systems in Colombia, resulting in the description of new species of terrestrial isopods. For the assessment of taxonomic and functional diversity, specimens from PETAR were used. The analyses included the effective species number structure based on Hill numbers, and functional diversity metrics (FRic, FEve, and FDiv) by habitats, in addition to the estimation of taxonomic and functional dissimilarity by habitats using the Baselga approach. Functional distance was calculated using Gower distance. All analyses were performed using RStudio v. 4.4.1 software. Regarding the first purpose, the examination of specimens from Colombia resulted in the description of new species of terrestrial isopods of the genus Ctenorillo, with a publication in the journal Tropical Zoology. For the second purpose, the study of specimens from southeastern Brazil identified 309 individuals belonging to 29 species, five families, and nine genera, mainly from subterranean habitats in the Atlantic Forest, especially PETAR, in the state of São Paulo. These data formed the basis of an article on the oniscid fauna of the Alto Ribeira region, including PETAR, PEI, PECD, and contiguous areas, with the description of three new species and new records for the karst area of Alto Ribeira. For the third purpose, the results indicated greater functional richness in epigean assemblages, while beta diversity was high in both taxonomic and functional dimensions. This pattern was mainly driven by species turnover, highlighting marked differentiation in the structure of assemblages between habitats. Principal Coordinate Analysis revealed partial segregation of epigean and hypogean assemblages in functional space, as well as grouping of traits by family, highlighting the role of evolutionary history in shaping functional composition. These results contribute to the understanding of the mechanisms that structure biodiversity along environmental gradients in the Atlantic Forest and reinforce the importance of integrating taxonomic and functional perspectives to guide conservation actions. The simultaneous protection of epigean and hypogean habitats in threatened karst systems is essential to preserve biological diversity and the ecological processes that sustain these ecosystems. Finally, the knowledge generated by this work offers tools for decision-making in conservation policies for strategic areas, management of tropical subterranean habitats, and mitigation of the effects of climate change.
Taxonomic composition and functional variations of terrestrial isopods (Isopoda: Oniscidea) in epigean and hypogean habitats of the Neotropical region
Keywords: Alfa funcional; Beta funcional; Habitat epígeo; Habitat hipógeo; Isópodes terrestres; Mata Atlântica; CIENCIAS BIOLOGICAS::ECOLOGIA; 15. Vida Terrestre